Catalog to families, genera, and species of orders Actiniaria and Corallimorpharia (Cnidaria: Anthozoa) - Fautin, Daphne Gail (Zootaxa, 2016)
This book inventories all available (and some unavailable) names in the family, genus, and species groups of extant members of orders Actiniaria and Corallimorpharia [cnidarian subclass Hexacorallia (Zoantharia) of class Anthozoa], providing a benchmark of names, their status, and taxon membership. I have attempted to make the compilation complete as of 2010; some names created after 2010 are included. The book is derived from a database I compiled that was available through a website. Most of the book is from the literature that defines taxa and documents their geographic distribution—primarily publications on nomenclature, taxonomy, and biogeography, but also some on ecology, pharmacology, reproductive biology, physiology, etc. of anemones (the common name for these groups); the reference section comprises 845 entries. As for previous anemone catalogs, this contains taxonomic as well as nomenclatural information, the former based on subjective opinion of working biologists, the latter objectively verifiable and unchanging (except by action of the International Commission on Zoological Nomenclature). Each family-group name, genus-group name, and original combination for species-group names has an entry. The entry contains the bibliographic reference to the publication in which each name was made available. This book contains for Corallimorpharia seven family names (four considered valid [57%]), 20 generic names (10 considered valid [50%] and one unavailable), and 65 species names (46 considered valid [70%]). It contains for Actiniaria 86 family names (50 considered valid [58%] and three unavailable), 447 generic names (264 considered valid [59%] and two unavailable), and 1427 species names (1101 considered valid [77%] and nine unavailable). Type specimens are inventoried from more than 50 natural history museums in Africa, Australia, Europe, New Zealand, and North America, including those with the largest collections of anemones; the geographic sources of specimens that were the bases of new names are identified. I resolve some nomenclatural issues, acting as First Reviser. A few taxonomic opinions are published for the first time. I have been unable to resolve a small number of problematic names having both nomenclatural and taxonomic problems. Molecular phylogenetic analyses are changing assignment of genera to families and species to genera. Systematics may change, but the basics of nomenclature remain unchanged in face of such alterations. All actions are in accord with the principles of nomenclature enunciated in the International Code of Zoological Nomenclature. These include the type concept, the Principle of Coordination, and the Principle of Priority. Nomenclatural acts include the creation of new replacement names; seven actiniarian generic names and one species name that are junior homonyms but have been treated as valid are replaced and an eighth new genus name is created. I designate type species for two genera. Except for published misspellings, names are rendered correctly according to the International Code of Zoological Nomenclature; I have altered spelling of some species names to conform to orthographic regulations. I place several species that had been assigned to genera now considered junior synonyms in the genus to which the type species was moved; experts on these anemones should determine whether those generic placements, which follow the nomenclatural rules, are taxonomically appropriate. This inventory can be a useful starting point in assembling the literature and trying to understand the rationale for the creation and use of names for the taxonomic matters yet to be resolved. Some nomenclatural conundra will not be resolved until taxonomic uncertainties are. A taxonomist familiar with the animals needs to ascertain whether the published synonymies are justified. If so, the senior synonym should be used, which, in many instances, will involve determining the proper generic assignment of the species and the correct rendering of the name; if changing the name would be disruptive, retaining the junior name would require an appeal to the Commission (Code Article 23.11).